1970
DOI: 10.3329/bjo.v14i2.3281
|View full text |Cite
|
Sign up to set email alerts
|

Ludwig’s Angina: a study of 50 cases

Abstract: Dental infection was documented as the most common cause (70%) of Ludwig's angina, followed by infection of the tonsils (10%) and submandibular gland (6%). Systemic illnesses included diabetes mellitus (30%) and chronic renal failure (4%).Streptococcus is commonest organism found in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…However, our findings are consistent with earlier reports showing male adults preponderance with sporadic incidents in children 11,12,14 . Here male to female ratio was 4:56:1, which was nearly consistent to the previous studies in our country as 2:57:1 by Fakir et al 15 Ludwig's angina can arise from various sources such as odontogenic infection 2 or complicated cases of submandibular 3 gland sialadenitis and sialolithisasis, tongue base lymphangioma, and tongue piercing 12,15,17, but several studies report our finding that there is usually a dental focus of infection 2,14 . We found 64(74.2%) patients were suffered from dental carious which simulated of the previous study by Fakir et al 15 .…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings are consistent with earlier reports showing male adults preponderance with sporadic incidents in children 11,12,14 . Here male to female ratio was 4:56:1, which was nearly consistent to the previous studies in our country as 2:57:1 by Fakir et al 15 Ludwig's angina can arise from various sources such as odontogenic infection 2 or complicated cases of submandibular 3 gland sialadenitis and sialolithisasis, tongue base lymphangioma, and tongue piercing 12,15,17, but several studies report our finding that there is usually a dental focus of infection 2,14 . We found 64(74.2%) patients were suffered from dental carious which simulated of the previous study by Fakir et al 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Patients of poor socioeconomic status comprised 70% in a study of 50 cases of Ludwig's angina. 15 In the present study, most of patients were from rural background. The largest group consisted of patients in 21 to 30 years of age.…”
Section: Discussionmentioning
confidence: 57%
“…A study done by Fakir et al on 50 cases of Ludwig's angina showed neck swelling, pain in neck and fever in 100% cases, whereas dysphagia was present in 80%. 15 In another study done by V Sharma fever and neck swelling was present in 100% cases, halitosis was present in 68% cases, difficulty in swallowing was present in 63.8% of cases, hoarseness of voice was present in 61.7% cases. Trismus was present in 36.2% of cases and respiratory difficulty in 8.5% of cases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations